Beach Erosion Characteristics Induced by Human Activities—A Case Study in Haiyang, Yellow Sea - Changle Zhang; Yongzhi Wang; Jun Du; Ziwen Tian; Yi Zhong (Remote Sensing)
Coastal zones, which serve as transitional areas between land and sea, possess unique ecological values. Sandy coasts, celebrated for their distinctive natural beauty and ideal recreational settings, have garnered significant attention. However, uncontrolled human activities can exacerbate erosion or even trigger more severe erosion along these coasts. This study utilizes unmanned aerial photography and typical beach profile survey data collected from the main areas of Wanmi Beach over the past eight years to quantify annual changes in beach erosion and elucidate the erosion characteristics and their variations across different shore profiles. Additionally, the impact of various types of human activities in different regions is analyzed, revealing the erosion patterns prevalent in the main areas of Wanmi Beach. The findings indicate that the eastern research area (ERA) has been in a continuous state of erosion, primarily due to a reduction in sediment supply in the region, with severe erosion observed on the foreshore of Fengxiang Beach and Wanmi Bathing Beach (WBB). In contrast, the central research area (CRA), particularly around Yangjiao Bay, has experienced significant siltation in recent years, with the highest siltation volume recorded between 2021 and 2023, totaling 90,352.91 m3. Nevertheless, the foreshore areas at both ends of the research area, distant from Yangjiao Bay, have been subject to erosion. The western research area (WRA) is notably impacted by surrounding aquaculture activities, leading to alternating periods of erosion and siltation on the beach surface. Consequently, due to the influence of human activities on different shore profiles, most of Wanmi Beach, except for the area near Yangjiao Bay, is experiencing erosion.